Trespasses : featuring Tangara Ensemble - string quartet - Tasdance (Company) ([Launceston, Tas.] : Tasdance, 1992)
Poster advertising Tasdance's production "Trespasses" with the Tangara Ensemble. Includes event details for performances at Launceston's Princess Theatre, Melbourne's George Fairfax Studio and Hobart's Theatre Royal, August-September 1992. Features black and white image of two dancers - one flipping the other over their back - set in front of a circular no symbol in red. Performance details appear adjacent the top edge of the no symbol. "Trespasses" appears vertically along the right hand edge.
Caption title.
Keywords: Tasdance (Company) -- Performances -- Tasmania -- Posters; Tasdance (Company) -- Performances -- Victoria -- Melbourne -- Posters; Posters, Australian; Dance -- Tasmania -- Posters; Dance -- Victoria -- Melbourne -- Posters; Australia -- Posters; Australian